2008
DOI: 10.1111/j.1742-4658.2008.06258.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of four type 2 ribosome inactivating pulchellin isoforms from Abrus pulchellus seeds

Abstract: Abrus pulchellus seeds contain at least seven closely related and highly toxic type 2 ribosome‐inactivating pulchellins, each consisting of a toxic A‐chain linked to a sugar binding B‐chain. In the present study, four pulchellin isoforms (termed P I, P II, P III and P IV) were isolated by affinity, ion exchange and chromatofocusing chromatographies, and investigated with respect to toxicity and sugar binding specificity. Half maximal inhibitory concentration and median lethal dose values indicate that P I and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
1
11
0
3
Order By: Relevance
“…The mechanism (ribosome-inactivating effects) of the toxicity of pulchellin is similar to that of ricin and abrin introduced above with some variations (also see Araújo et al, 2010;Castilho et al, 2008;Silva et al, 2005). Stirpe et al (2007) isolated, purified and identified stenodactylin and lanceolin [which are highly toxic to cells (in which they induce apoptosis) and to mice] from the caudices of Passifloraceae Adenia lanceolata and A. stenodactyla, respectively.…”
Section: Pulchellinmentioning
confidence: 68%
See 1 more Smart Citation
“…The mechanism (ribosome-inactivating effects) of the toxicity of pulchellin is similar to that of ricin and abrin introduced above with some variations (also see Araújo et al, 2010;Castilho et al, 2008;Silva et al, 2005). Stirpe et al (2007) isolated, purified and identified stenodactylin and lanceolin [which are highly toxic to cells (in which they induce apoptosis) and to mice] from the caudices of Passifloraceae Adenia lanceolata and A. stenodactyla, respectively.…”
Section: Pulchellinmentioning
confidence: 68%
“…The mechanism (ribosome‐inactivating effects) of the toxicity of pulchellin is similar to that of ricin and abrin introduced above with some variations (also see Araújo et al ., ; Castilho et al ., ; Silva et al ., ).…”
Section: Scientific Proof Of Toxic Plant Proteinmentioning
confidence: 99%
“…Previous reports suggest that up to four distinct abrin and pulchellin protein isoforms exist. Both of these proteins have been shown to be toxic to human/primate cell lines and during mouse assays at varying levels, depending on the abrin [7] and pulchellin [8] isoforms isolated. Furthermore, agglutinin, an evolutionary variant of pulchellin and abrin, has been shown to be less toxic due to the lack of a critical hydrogen bond that causes a lower binding in between Abrin and 28S RNA [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the mid-2000s, the Araújo Lab at the University of Sao Paulo cloned and expressed the A-and B-chains of pulchellin (orthologs of abrin genes) to test the toxicity of the compounds produced by the related species Abrus pulchellus. This group subsequently sequenced four mRNA prepropulchellin types [8,14,15]. Additional sequencing of standard plant genetic barcode regions for species identification and phylogenetic analysis are in abundance in GenBank as well, but complete genome sequencing and assembly of an Abrus genome has not been completed to date.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies of endocytosis and intracellular transport of Pulchellin have been done in the Institute of Physics in Sao Carlos, University of Sao Paulo. (26)(27)(28) It is assumed that the mechanism of Pulchellin for entering target cells would be similar to ricin.…”
Section: Transport Of Protein Rips Into Cellsmentioning
confidence: 99%